Entrepreneurship as Moral Practice: An Existential Phenomenological Study of Meaning, Care, and Digital Agency among Women MSME Entrepreneurs in Makassar - Dipoatmodjo, Tenri Sayu Puspitaningsih (Journal Management & Economics Review (JUMPER), 2025)
This study explores the lived meanings of work and entrepreneurship among women-led micro, small, and medium enterprises (MSMEs) in Makassar through an existential phenomenological approach. Beyond income generation, these enterprises are moral and relational projects in which women negotiate identity, care, and purpose amid digital transformation and structural constraint. Fourteen female entrepreneurs from culinary, crafts, fashion, and digital micro-service sectors were interviewed and observed to capture first-person accounts of their entrepreneurial experiences. The analysis identified five key themes: work as moral and identity work, care-oriented agency, digital practices as meaningful mediators, resilience through ritual and narrative, and aspirational freedom within constraint. Findings reveal that entrepreneurship among these women embodies a form of moral economy grounded in dignity, familial responsibility, and community reciprocity. Digitalization emerged as both an enabler of creative expression and a new domain of vulnerability, underscoring the need for socially attuned and trust-based digital ecosystems. The study contributes to humanistic economics by framing women’s entrepreneurship as existential and relational labor, offering insights for policies and training programs that integrate financial inclusion, digital literacy, and psychosocial mentorship. Ultimately, it argues that inclusive economic development must center human meaning and moral purpose, not merely productivity metrics.